Linear Algebra: Matrix Inverses and Determinants PDF
Document Details
Uploaded by Deleted User
Tags
Summary
This document provides notes on matrix inverses and determinants. It includes definitions, detailed theorems, and illustrated examples. It covers a range of topics in linear algebra, suitable for university-level study.
Full Transcript
# Section 2.2 ## Definition: An *n x n* matrix *A* is **invertible** or **non-singular** if there is an *n x n* matrix *C* satisfying *CA* = *I<sub>n</sub>* and *AC* = *I<sub>n</sub>*. If such a *C* exists it is unique and called the **inverse of A**. The inverse of *A* is denoted *A<sup>-1</sup>...
# Section 2.2 ## Definition: An *n x n* matrix *A* is **invertible** or **non-singular** if there is an *n x n* matrix *C* satisfying *CA* = *I<sub>n</sub>* and *AC* = *I<sub>n</sub>*. If such a *C* exists it is unique and called the **inverse of A**. The inverse of *A* is denoted *A<sup>-1</sup>*. If *A* is not invertible it is called **Singular**. ## Theorem: If *A* is an invertible *n x n* matrix then for every *b* ∈ ℝ<sup>n</sup>, *Ax = b* has the unique solution *x = A<sup>-1</sup>*b. In particular, *A* has *n* pivots (one in every row and one in every column) and its *rref* is *I<sub>n</sub>*. If *A*<sup>-1</sup> = *B* then *Ax = A(A<sup>-1</sup>b) = (AA<sup>-1</sup>)b = I<sub>n</sub>b = b* If *Ax = b* then *A<sup>-1</sup>(Ax) = A<sup>-1</sup>b *(AA<sup>-1</sup>)x = A<sup>-1</sup>b* *I<sub>n</sub>x = A<sup>-1</sup>b* *x = A<sup>-1</sup>b* ## Definition: The **determinant** of a 2 x 2 matrix $\begin{bmatrix}a & b \\ c & d \end{bmatrix}$ is *det* $\begin{bmatrix}a & b \\ c & d \end{bmatrix}$ = *ad - bc*. We will discuss determinants in general in Chapter 3. ## Theorem: If *A = $\begin{bmatrix}a & b \\ c & d \end{bmatrix}$* then *A* is invertible iff *det* *A* ≠ 0. If A is invertible *A<sup>-1</sup>* = $\frac{1}{det A}\begin{bmatrix}d & -b \\ -c & a\end{bmatrix}$ ## Example: Let *A* = **$\begin{bmatrix}3 & 4 \\ 2 & 1 \end{bmatrix}$**. Find *A<sup>-1</sup>*, if it exists. *det A* = 3·1 - 2·4 = -2 (≠0 so *A* is invertible) *A<sup>-1</sup>* = $\frac{1}{-2}\begin{bmatrix}1 & -4 \\ -2 & 3 \end{bmatrix}$ = **$\begin{bmatrix}-1/2 & 2 \\ 1 & -3/2\end{bmatrix}$** ## Example: Solve *x<sub>1</sub>* + 2*x<sub>2</sub>* = 5 3*x<sub>1</sub>* + 4*x<sub>2</sub>* = 6 This is *Ax = b* where *A* is as above. So Solution: *x* = *A<sup>-1</sup>b* = **$\begin{bmatrix}-1/2 & 2 \\ 1 & -3/2\end{bmatrix}$** $\begin{bmatrix}5 \\ 6 \end{bmatrix}$ = **$\begin{bmatrix}-13/2 \\ 9/2 \end{bmatrix}$** ## Theorem: If *A, B* are invertible *n x n* matrices then - *A<sup>-1</sup>* is invertible and *(A<sup>-1</sup>)<sup>-1</sup>* = *A* - *A<sup>T</sup>* is invertible and *(A<sup>T</sup>)<sup>-1</sup>* = *(A<sup>-1</sup>)<sup>T</sup>* - *AB* is invertible and *(AB)<sup>-1</sup>* = *B<sup>-1</sup>*A<sup>-1</sup> * (reverse order!)* ## Definition: An *n x n* **elementary matrix** is a matrix obtained by performing a single elementary row operation on *I<sub>n</sub>*. ## Example: Find the 2 x 2 elementary matrices corresponding to: Start with *I<sub>2</sub>* = **$\begin{bmatrix}1 & 0 \\ 0 & 1 \end{bmatrix}$** and apply each row operation - -4*R<sub>1</sub>* + *R<sub>2</sub>* -> *R<sub>2</sub>* **$\begin{bmatrix}1 & 0 \\ -4 & 1 \end{bmatrix}$** - *R<sub>1</sub>* ↔ *R<sub>2</sub>* **$\begin{bmatrix}0 & 1 \\ 1 & 0 \end{bmatrix}$** - 3*R<sub>2</sub>* -> *R<sub>2</sub>* **$\begin{bmatrix}1 & 0 \\ 0 & 3 \end{bmatrix}$** Next, multiply **$\begin{bmatrix}4 & 5 & 6 \\ 1 & 2 & 3\end{bmatrix}$** on the left by each of these matrices. - **$\begin{bmatrix}1 & 0 \\ -4 & 1 \end{bmatrix}$** $\begin{bmatrix}4 & 5 & 6 \\ 1 & 2 & 3\end{bmatrix}$ = **$\begin{bmatrix}4 & 5 & 6 \\ 0 & -18 & -21\end{bmatrix}$** - **$\begin{bmatrix}0 & 1 \\ 1 & 0 \end{bmatrix}$** $\begin{bmatrix}4 & 5 & 6 \\ 1 & 2 & 3\end{bmatrix}$ = **$\begin{bmatrix}1 & 2 & 3 \\ 4 & 5 & 6\end{bmatrix}$** - **$\begin{bmatrix}1 & 0 \\ 0 & 3 \end{bmatrix}$** $\begin{bmatrix}4 & 5 & 6 \\ 1 & 2 & 3\end{bmatrix}$ = **$\begin{bmatrix}4 & 5 & 6 \\ 3 & 6 & 9\end{bmatrix}$** ## Observation: Each elementary row operation has the same effect as multiplying on the left by the corresponding elementary matrix. Also, elementary matrices are invertible (since elementary row operations can be undone). ## Theorem: An *n x n* matrix *A* is invertible iff the *rref* of *A* is *I<sub>n</sub>*. Additionally, any sequence of row operations that turns *A* into *I<sub>n</sub>* will turn *I<sub>n</sub>* into *A<sup>-1</sup>*. Say *E<sub>1</sub>*, ..., *E<sub>k</sub>* are elementary matrices corresponding to row operations turning *A* into *I<sub>n</sub>*. Then *E<sub>k</sub>...E<sub>1</sub>E<sub>k</sub>...E<sub>1</sub>A = I<sub>n</sub>*. Set *B* = *E<sub>k</sub>...E<sub>1</sub>*. *B* is invertible, *BA* = *I<sub>n</sub>*. *B*<sup>-1</sup>*BA* = *B<sup>-1</sup>I<sub>n</sub>*. *I<sub>n</sub>A* = *B<sup>-1</sup>I<sub>n</sub>*. *A* = *B<sup>-1</sup>*, *A* is invertible. ## Algorithm for finding *A<sup>-1</sup>*: If *A* invertible, the *rref* of [A *I<sub>n</sub>*] is [I<sub>n</sub> A<sup>-1</sup>] ## Example: Find the inverse of *A* = **$\begin{bmatrix}1 & 0 & -2 \\ 0 & 1 & 1 \\ 2 & 3 & -1\end{bmatrix}$** if it exists. **$\begin{bmatrix}1 & 0 & -2 & 1 & 0 & 0 \\ 0 & 1 & 1 & 0 & 1 & 0 \\ 2 & 3 & -1 & 0 & 0 & 1\end{bmatrix}$** *R3 - 2R1* -> *R3* **$\begin{bmatrix}1 & 0 & -2 & 1 & 0 & 0 \\ 0 & 1 & 1 & 0 & 1 & 0 \\ 0 & 3 & 3 & -2 & 0 & 1\end{bmatrix}$** *R3 - 3R2* -> *R3* **$\begin{bmatrix}1 & 0 & -2 & 1 & 0 & 0 \\ 0 & 1 & 1 & 0 & 1 & 0 \\ 0 & 0 & 0 & -2 & -3 & 1\end{bmatrix}$** *R1 + 2R3* -> *R1* **$\begin{bmatrix}1 & 0 & -2 & -3 & -6 & 2 \\ 0 & 1 & 1 & 0 & 1 & 0 \\ 0 & 0 & 0 & -2 & -3 & 1\end{bmatrix}$** *R2 - R3* -> *R2* **$\begin{bmatrix}1 & 0 & -2 & -3 & -6 & 2 \\ 0 & 1 & 1 & 2 & 4 & -1 \\ 0 & 0 & 0 & -2 & -3 & 1\end{bmatrix}$** *-1/2R3* -> *R3* **$\begin{bmatrix}1 & 0 & -2 & -3 & -6 & 2 \\ 0 & 1 & 1 & 2 & 4 & -1 \\ 0 & 0 & 0 & 1 & 3/2 & -1/2\end{bmatrix}$** *R1 + 3R3* -> *R1* **$\begin{bmatrix}1 & 0 & -2 & 0 & -3/2 & 1/2 \\ 0 & 1 & 1 & 2 & 4 & -1 \\ 0 & 0 & 0 & 1 & 3/2 & -1/2\end{bmatrix}$** *R2 - 2R3* -> *R2* **$\begin{bmatrix}1 & 0 & -2 & 0 & -3/2 & 1/2 \\ 0 & 1 & 1 & 0 & 1 & 0 \\ 0 & 0 & 0 & 1 & 3/2 & -1/2\end{bmatrix}$** *A<sup>-1</sup>* = **$\begin{bmatrix}0 & -3/2 & 1/2 \\ 0 & 1 & 0 \\ 1 & 3/2 & -1/2 \end{bmatrix}$**